Pengaruh Pendidikan, Belanja Modal dan Pekerja Informal terhadap Tingkat Kemiskinan di Provinsi Nusa Tenggara Timur Tahun 2019-2024 dengan Covid-19 sebagai Variabel Dummy - Hesti Dwi Kurnianti; Herlitah Herlitah; Saparuddin M (Indo Publishing, 2026)
This study aims to analyse the effect of education, capital expenditure, informal workers, and the COVID-19 pandemic on the poverty rate in East Nusa Tenggara Province during the 2019–2024 period. A quantitative approach was applied using panel data regression analysis with a census technique on the entire population of 22 regencies/cities, yielding 110 observations. Utilizing secondary data from BPS and DJPK, the analysis included classical assumption tests, multiple linear regression, and hypothesis testing. The results indicate that education and informal workers have a negative and significant effect on poverty levels. Education improves community productivity, while the informal sector serves as a vital safety net providing alternative income sources. Conversely, capital expenditure has no significant impact on poverty because the benefits of public infrastructure development require a long-term period to materialize. Meanwhile, the COVID-19 pandemic had a positive and significant effect on increasing poverty due to economic disruptions and job losses. These findings imply the need for integrated policies prioritizing education quality, informal sector empowerment, capital expenditure effectiveness, and social protection. Future studies are recommended to add relevant variables such as the human development index, unemployment, or income inequality, and to extend the research period to comprehensively capture long-term impacts.